2020
DOI: 10.1029/2019gl086756
|View full text |Cite
|
Sign up to set email alerts
|

Clumped Isotopes Link Older Carbon Substrates With Slower Rates of Methanogenesis in Northern Lakes

Abstract: The release of long‐stored carbon from thawed permafrost could fuel increased methanogenesis in northern lakes, but it remains unclear whether old carbon substrates released from permafrost are metabolized as rapidly by methanogenic microbial communities as recently produced organic carbon. Here, we apply methane (CH4) clumped isotope (Δ18) and 14C measurements to test whether rates of methanogenesis are related to carbon substrate age. Results from culture experiments indicate that Δ18 values are negatively c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 58 publications
5
45
0
Order By: Relevance
“…The kinetic isotopologue signals from surface methane are consistent with those from laboratory culture experiments, in which methanogens consistently produced methane with non-equilibrium isotopologue compositions (Wang et al, 2015;Douglas et al, 2017Douglas et al, 2020Gruen et al, 2018;Stolper et al, 2015). Previous studies have also investigated the clumped methane isotopologue fractionation during sink reactions, including aerobic methane oxidation (Wang et al, 2016) and gas phase methane oxidation by OH and Cl radicals (Whitehill et al, 2017;Joelsson et al, 2014Joelsson et al, , 2016.…”
Section: Introductionsupporting
confidence: 66%
See 2 more Smart Citations
“…The kinetic isotopologue signals from surface methane are consistent with those from laboratory culture experiments, in which methanogens consistently produced methane with non-equilibrium isotopologue compositions (Wang et al, 2015;Douglas et al, 2017Douglas et al, 2020Gruen et al, 2018;Stolper et al, 2015). Previous studies have also investigated the clumped methane isotopologue fractionation during sink reactions, including aerobic methane oxidation (Wang et al, 2016) and gas phase methane oxidation by OH and Cl radicals (Whitehill et al, 2017;Joelsson et al, 2014Joelsson et al, , 2016.…”
Section: Introductionsupporting
confidence: 66%
“…The ln(γAOM) values from this study (-4.8 to -12.8 ‰, Table 2) and experimentally derived ln(γmtg) values of -3.8 to +2.3 ‰ for hydrogenotrophic methanogenesis (Gruen et al, 2018;Douglas et al, 2020) yield the range of the Δ 13 CH3D value from +1.0 to +15.1 ‰. Most environmental data show Δ 13 CH3D values smaller than ca.…”
Section: Methane Isotopologue Compositions As a Results Of Kinetic Framentioning
confidence: 51%
See 1 more Smart Citation
“…Based on this, we estimate a typical error for δ 2 H-CH 4 data of less than 3 ‰. Studies where data were derived from graphs are identified in Supplement Table S1 (Douglas et al, 2020b).…”
Section: Dataset Structurementioning
confidence: 99%
“…Although microbial methane is often in clumped isotope disequilibrium Wang et al, 2015;Douglas et al, 2016;Young et al, 2017), microbial methane found in marine and/or subsurface environments is usually in or close to equilibrium. It has been proposed that slow anaerobic coupled methanogenesis and methanotrophy in nature under low thermodynamic drive (e.g., H 2 supply) could drive methane to internal isotopic equilibrium at its environmental temperature (e.g., Gruen et al, 2018;Giunta et al, 2019;Douglas et al, 2020). Besides that, microbes degrading C 2 -C 4 short alkanes have been found in the Gulf of Mexico sediments (Kniemeyer et al, 2007;Laso-Pérez et al, 2016;Chen et al, 2019).…”
Section: Biological Degradationmentioning
confidence: 99%